Strain Sensors: Meso‐Reconstruction of Wool Keratin 3D "Molecular Springs" for Tunable Ultra‐Sensitive and Highly Recovery Strain Sensors (Small 24/2020). Issue 24 (18th June 2020) - Zhang, Lin; Hu, Fan; Zhu, Shuihong; Lin, Youhui; Meng, Zhaohui; Yu, Rui; Liu, Xiang Yang
Abstract : In article number 2000128, Youhui Lin, Xiang Yang Liu, and co‐workers successfully create 3D "molecular springs" networks by establishing crosslinks of scattered wool keratin. The as‐prepared networks display unique elasticity, high resistance fatigue, fast self‐recovery, and ultralow effective elastic modulus. Due to the fascinating features, such wool keratin mediated materials can be used in the construction of reliable and highly sensitive strain sensors with broad sensing ranges.